Máximo déficit acumulado de oxigênio em corridas livre e resistida em pista - Ribeiro, Luiz Fernando Paulino [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Maximal accumulated oxygen deficit (MAOD) is nowadays taken as the gold standard measure of anaerobic capacity in humans. Namely, the abbreviated procedure known as the procedure #3 by Medbø, seems an interesting testing option for athletes due to practical reasons. But besides the relevance of specificity and the increasing use of portable gas analyzers for the assessment of aerobic parameters in field conditions, information on MAOD assessment, precision or validity in track tests are not available. Thus, the aims of this study were: i) to assess MAOD and its precision in runners by means of the procedure #3 adapted to the track; ii) to analyze the effects of variations regarding the use of resting VO2 (VO2REP) on the regressions used in the MAOD estimation and; iii) to analyze the concurrent validity of such measure by comparing the values attained in free (CL) and resisted (CR) running tests. In a two-week period, 8 sprint runners (21.5 ± 3.2 years; 71.5 ± 6.0 kg; 180 ± 6 cm and 4.9 ± 1.3 % fat) were subjected to 6 experimental sessions separated by 48 - 72 h on a 400 m track, being 3 evaluations carried out in the CL and 3 in the CR conditions. In the later one, a mobile device was used in order to impose an horizontal resistance of 4 % body weight to the subjects. In all tests the VO2 was monitored by means of a portable analyzer using telemetry. Incremental tests were performed in both conditions for the assessment of VO2PICO and vVO2PICO. Linear regressions between velocity and VO2 were determined from 3 submaximal efforts lasting 6 min between ~75 to 96% VO2PICO with and without VO2REP at zero velocity for the estimation of oxygen demand (DO2) for intensities of 120 and 110% vVO2PICO in CL and CR, respectively. Finally, exhaustive bouts at such intensities were carried out being the MAOD computed as the difference between total DO2 (DO2TOT) and accumulated oxygen uptake (VO2AC). Both in CL and CR, the inclusion of VO2REP...

O máximo déficit acumulado de oxigênio (MAOD) é tido atualmente como medida padrão-ouro para diagnóstico da capacidade anaeróbia (CAn) em humanos. Particularmente o procedimento abreviado conhecido como #3 de Medbø constitui, por razões práticas, interessante opção de avaliação em atletas. Mas apesar da relevância da especificidade e crescente emprego de analisadores de gases portáteis na determinação de índices aeróbio em de campo, não são encontradas na literatura informações relativas à determinação, precisão ou validade do MAOD em pista de atletismo. Assim, foram objetivos do presente estudo: i) a determinação do MAOD e sua precisão em corredores por meio do procedimento #3 adaptado à pista; ii) análise da influência de variações quanto à inclusão de valores VO2 de repouso (VO2REP) nas regressões necessárias ao cálculo do MAOD e; iii) análise da validade concorrente do MAOD confrontando os valores obtidos em corrida livre (CL) aos verificados em teste de corrida resistida (CR). Num intervalo de duas semanas, 8 velocistas (21,5 ± 3,2 anos; 71,5 ± 6,0 kg; 180 ± 6 cm e 4,9 ± 1,3 % de gordura) foram submetidos a 6 sessões experimentais separadas por 48 a 72 horas em pista de 400 m, sendo 3 avaliações em CL e 3 em CR. Nesta última foi utilizado aparato móvel com intuito de impor de resistência horizontal de 4 % do peso corporal ao deslocamento dos voluntários. Em todas as avaliações o VO2 foi monitorado por meio de analisador portátil em modo de telemetria. Testes incrementais contínuos em ambas as condições foram realizados para determinação do VO2PICO e vVO2PICO. Regressões lineares velocidade-VO2 individuais foram calculadas a partir de 3 esforços submáximos de 6 min entre ~75 e 96% do VO2PICO com e sem VO2REP na velocidade zero para estimativa da demanda de oxigênio (DO2) para intensidades equivalentes a 120 e 110% da vVO2PICO em CL e CR, respectivamente. Finalmente, esforços...
Keywords: Running; Corridas; Capacidade anaeróbica; Aptidão física do atleta; Oxigenio; Fisiologia